Teacher Strategies and Student Preferences in Overcoming Disruptive Behavior of Elementary School Students - Khotimah, Nur; Endang Fauziati; Choiriyah Widyasari; Minsih (Universitas Pendidikan Ganesha, 2023)
The background of this study is that there are still many students who carry out disruptive activities during the learning process. Disruptive behaviour in the classroom can adversely affect the learning process and affect the performance of students, teachers, and the class as a whole. This study is aim to analyse teacher's strategies and student preferences regarding disruptive behaviour in elementary school students. This method uses a qualitative approach with a case study design. The subjects included students and teachers of grade 4 at elementary school. The data collection techniques are using observation and interviews. The data analysis techniques include data reduction, data display, and data verification. The results of this study show that the teacher's strategy in overcoming disruptive behaviour uses three approaches, namely behavioristic, cognitive, and humanistic. Student preference in dealing with disruptive behaviour lies in the problem of learning styles that must be adapted to the way teachers teach their students. This has implications going forward so that in the learning process, teachers can use a variety of learning approaches in order to minimize disruptive behaviour by students in the classroom. If disruptive behaviour is ignored, it will be difficult to overcome it later.